2013
DOI: 10.1007/s11064-013-0970-y
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Properties of New Chemical Entity, 5TIO1

Abstract: 2-[(2,6-dichlorobenzylidene)amino]-5,6-dihydro-4H-cyclopenta[b]thiophene-3-carbonitrile), 5TIO1, is a new 2-aminothiophene derivative with a promising pharmacological activity. The aim of this work was to evaluate the potential anxiolytic effect of 5TIO1 in animal models. In the elevated plus-maze test, 5TIO1 (0.1, 1.0 and 10.0 mg/kg, i.p) increased the time of permanence and the number of entries in the open arms. In the light/dark box test, 5TIO1 at dose of 0.1 mg/kg (i.p) also showed anxiolytic-like effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Our results observed neurochemical alterations after administration of an anxiolytic-like compound, 5TIO1 [23]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results observed neurochemical alterations after administration of an anxiolytic-like compound, 5TIO1 [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Drug dosages of 5TIO1 were determined from dose-response studies (data not shown) and from observation of dose currently used in animal's studies [23–25]. The doses of 5TIO1 used (0.1, 1, and 10 mg/kg) in the present study are not equivalent to those used by humans because rats have different metabolic rates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The open field arena (100 cm × 100 cm × 40 cm) is constructed of acrylic, with gray walls and a black floor, which is divided into 25 squares of equal areas as previously described [25, 26]. Instances of crossing-movement (Cm) and instances of rearing-movement (Rm) are usually used as measures of exploration and anxiety [27, 28].…”
Section: Methodsmentioning
confidence: 99%
“…In recent drugs investigations, they acquired a particular importance due to the innovations in their synthesis (Gewald reaction), availability, stability, and structural simplicity that allow them to be important scaffolds in chemical and therapeutic products; like the top selling drugs olanzepine and tinoridine. [16][17][18] In addition, they present a large spectrum of biological properties that include antimicrobial, 19,20) anti-inflammatory, 21) anxiolytic, 22) antileishmanial, 23) anti-diabetes, 24) antifungal, 25) antioxidant 26) and antiplatelet activities. 27) The antitumor evaluation of the 2-aminothiophenes has already been addressed through different reports.…”
mentioning
confidence: 99%